Design of pH Sensitive Electrochemical Sensor for Catecholamine Neurotransmitters Detection and the Screening Off of Ascorbic Acid - Tshenkeng, Keamogetse Tebogo Charlotte (Rhodes University, Faculty of Science, Department of Chemistry)
This study presents the synthesis of cobalt (II) tetra-(3-carboxyphenoxy) phthalocyanine (CoTCPhOPc) through the cyclotetramerization of 4-(3-carboxyphe-noxy)phthalonitrile and its full characterization using Fourier transform infrared (FT-IR) spectroscopy, ultraviolet-visible (UV-vis) spectroscopy, magnetic circular dichroism (MCD) spectroscopy, elemental analysis and mass spectrometry. The CoTCPhOPc was then immobilized onto phenylethylamino (PEA) pre-grafted gold electrode surface, Au-PEA using amide coupling reaction through a reaction with NHS and DCC to obtain Au-PEA-CoTCPhOPc. This yielded pH sensitive thin films due to the terminal carboxylic acid ("“COOH) functional groups. Electrochemical and surface characterization was conducted to confirm the modification of the bare Au with PEA thin film (Au-PEA) and amide coupling of CoTCPhOPc (Au-PEA-CoTCPhOPc). The Au-PEA-CoTCPhOPc electrode was shown to possess pH selective properties towards negatively charged [Fe(CN)6]3-/4- and positively charged [Ru(NH3)6]2+/3+ redox probes. Au-PEA-CoTCPhOPc electrode surface enabled the detection of catecholamine neurotransmitters (dopamine, norepinephrine and epinephrine) and the screening off of ascorbic acid by means of pH sensitive functional groups. Bare Au and Au-PEA electrodes exhibited electro-oxidation and electroreduction of catecholamine neuro-transmitters and ascorbic acid at higher potentials compared to Au-PEA-CoTCPhOPc. There was no electro-oxidation or electroreduction of ascorbic acid at Au-PEA-CoTCPhOPc. For Au-PEA-CoTCPhOPc, excellent electrocatalytic oxidation with the limit of detection (LoD) determined using 3Ïƒ was found to be 1.32 (0.95), 2.11 (1.78) and 3.08 Î¼M for electro-oxidation and electroreduction (in brackets) of dopamine, norepinephrine and epinephrine respectively. The limit of quantification (LoQ) was determined using 10Ïƒ and found to be 4.41 (3.17), 7.02 (5.93) and 10.3 Î¼M electro-oxidation and electroreduction (in brackets) for dopamine, norepinephrine and epinephrine respectively. The Au-PEA-CoTCPhOPc thin film was shown to screen off ascorbic acid as no electrocatalytic oxidation was observed for up to 100.0 Î¼M concentration.
Keywords: Catecholamines; Electrochemical sensors; Neurotransmitters; Vitamin C; Cobalt; Phthalocyanines; Cobalt (II) tetra-(3-carboxyphenoxy) phthalocyanine (CoTCPhOPc)